2017
DOI: 10.7705/biomedica.v38i0.3593
|View full text |Cite
|
Sign up to set email alerts
|

Bronze baby syndrome, an unpredictable complication of phototherapy: A case report

Abstract: The bronze baby syndrome is an infrequent dyschromia resulting from phototherapy in newborn babies with neonatal jaundice. Even though the common phenotype has been described in patients with direct neonatal hyperbilirubinemia secondary to cholestasis, several cases of patients with indirect neonatal hyperbilirubinemia who have managed to reverse it have been reported, as well as patients with isolated hyperbilirubinemia.Currently, the physiopathology of this condition is still a subject of controversy and, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Despite BBS being considered a self‐limiting process, there is no consensus on when to start and stop phototherapy treatment. Although some authors have recommended stopping phototherapy, 3 most of them suggest continuing phototherapy to decrease bilirubin levels and reduce the risk of exchange transfusion 4 …”
Section: Discussionmentioning
confidence: 99%
“…Despite BBS being considered a self‐limiting process, there is no consensus on when to start and stop phototherapy treatment. Although some authors have recommended stopping phototherapy, 3 most of them suggest continuing phototherapy to decrease bilirubin levels and reduce the risk of exchange transfusion 4 …”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by bilirubin's spectral absorbance, which does not extend to wavelengths of 500nm. 1 On the other hand, Bronze baby syndrome (BBS) is an unusual condition developed in neonates with elevated serum levels of unconjugated and conjugated bilirubin treated with phototherapy [2][3][4] . Although the exact etiology of BBS is still unknown, there are possible explanations about why bronze skin colour may occurs.…”
Section: Discussionmentioning
confidence: 99%
“…8 Despite BBS is considered a self-limiting process there is not consensus on stopping or not phototherapy treatment. Although some authors have recommended stopping phototherapy 3 , most of them recommend continuing phototherapy to decrease bilirubin levels and so the risk of exchange transfusion 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Le and Reese [3] suggested that development of BBS should not lead to suspension of the use of phototherapy for hyperbilirubinemia in infants with elevated conjugated bilirubin levels. Conversely, Peinado-Acevedo et al [10] stated that the continuation of phototherapy presented a risk of cholestasis to newborns with BBS and recommended that it be suspended; however, phototherapy can be reinitiated when the direct bilirubin level decreases and cholestasis has resolved. It is not clear whether phototherapy should be continued or stopped in BBS.…”
Section: How Should Bbs Be Treated?mentioning
confidence: 99%